Bioindication and Biomonitoring of the Aquatic Environment - Bouaguel Leila (/, 2024)
This course content examines bioindication and biomonitoring as essential approaches for assessing the ecological quality of aquatic environments. It focuses on the biological responses of aquatic organisms to environmental stressors, particularly pollutants of anthropogenic origin. The document introduces key concepts such as bioindicators, biointegrators, bioaccumulators, and biomarkers, and explains their role in detecting, evaluating, and predicting ecosystem disturbances. It also addresses the effects of pollutants on populations, including toxicity assessment, interspecific interactions, tolerance, and resistance. Particular attention is given to pollutant monitoring in aquatic biotopes, the use of parasites as indicators of ecosystem quality, bioassays, physiological and biochemical biomarkers, and the prediction of bioaccumulation in trophic networks. The content further discusses xenobiotics and endocrine disruptors, especially their effects on reproductive and hepatic systems. Overall, the course provides a scientific framework for understanding how aquatic ecosystems respond to contamination and how biological tools can support environmental risk assessment and ecosystem management
/
This teaching material is designed for Master’s students in Aquatic Ecosystems. It provides a structured overview of bioindication and biomonitoring methods used to evaluate aquatic ecosystem health. The content combines ecological, physiological, and toxicological perspectives to explain how living organisms can reveal pollution effects and environmental degradation. It covers theoretical concepts, practical monitoring tools, toxicity tests, biomarkers, bioaccumulation processes, in situ experimentation, and the ecological impact of endocrine disruptors.
Keywords: Aquatic biomonitoring Bioindication Bioindicators Bioaccumulation Biomarkers Ecotoxicology Xenobiotics Endocrine disruptors